Preoperative Localization of Recurrence in the Thyroidectomy Bed Using a Radioactive Iodine125 Seed. (August 2018) - Garner, Hillary W.; Paz-Fumagalli, Ricardo; Young, Geoffrey D.
Intraoperative localization of nonpalpable recurrent thyroid cancer has been reported using needle localization, intraoperative ultrasound (US), dye injection, and radio-guided surgery. We describe the alternative technique of radioactive seed localization (RSL) in 3 patients with residual or recurrent papillary thyroid cancer. This technique has been used for many years in the setting of nonpalpable breast cancer, where it has been shown to be safe and has been associated with greater surgeon satisfaction as well as improved patient tolerability, cosmesis, and outcomes compared to needle localization. In addition, RSL allows complete decoupling of the radiology and surgery schedules. RSL was successful in our 3 patients with regard to safety, patient tolerability, and scheduling.